Education in Ukraine: Quality Assessment and Development Prospects. Based on PISA‑2018 - Valery Novikov; Yelena Makarova (Вопросы образования, 2020)
In 2018, Ukraine joined the Program for International Student Assessment (PISA). The results of PISA‑2018 showed that Ukraine performed below the OECD average in all areas of literacy: reading, mathematics, and science. This outcome did not meet the public expectations. The expert society has not yet fully realized the critical potential of the obtained PISA results or started a broad discussion to evaluate them and outline the avenues for education reforms. The article analyzes the PISA‑2018 performance of Ukrainian students in reading, mathematics and science literacy, as well as gender inequality, social contexts of learning, student resilience and achievement. Comparison of Ukraine’s educational practices with those of EU countries, reference countries and Russia is used to identify the common features of national education system development at the present-day stage and determine the specific aspects of institutional evolution in Ukrainian education. Public investment in education is analyzed and possible ways of improving its effectiveness are demonstrated. National education policy could be enhanced by updating the learning standards and competencies, raising teacher pay and extending professional development opportunities for teachers, increasing teacher motivation, developing the infrastructure, improving the inter-budgetary relations, and ensuring better performance assessment results.